Integrating into a global learning community: emerging perspectives for enhancing the interaction discourse in distance learning pedagogy (2019)
Interaction has been recognised as one of the most important components of learning experiences in distance education. Three types of interaction in distance education have been recognised in literature as learner-content, learner-tutor/instructor, and learner-learner interaction. This paper, therefore, proposed the expansion of these three types of interaction to include two additional types: learner-technology interaction and learner- institution interaction. The paper also discussed the importance of interaction in distance learning pedagogy as well as the theoretical guide which informed the justification of interaction in distance learning pedagogy. It further discussed the components of each type of interaction and, thereafter, recommended some strategies for enhancing each type. The paper concluded that the relevance of distance learning rests on the quality of interaction provided by distance learning institutions and suggested that practitioners and managers of distance learning institutions should pay more attention to the recommended strategies identified in the paper.